Transitional Spaces: Blurring the Line Between Interior and Exterior - Tucker, Lisa M. (Enquiry The ARCC Journal for Architectural Research, 2012)
This paper examines the transition spaces for homes between inside and outside designed by architects during the early twentieth century in the United States. Beginning in the late nineteenth century, the plan book became a readily available option for those wishing to build their own home in the U.S. Following a shortage of single-family houses after World War I, the design of small, single-family houses were distributed primarily through the plan book vehicle. One such plan book-producing group was the Architects’ Small House Service Bureau (ASHSB). The bureau was composed entirely of registered architects and produced multiple folios of small house plans between 1914 and 1942. This paper focuses specifically on the relationship between the interior spaces and outdoors through the use of loggias, pergolas, sun porches, bay windows and other devices. The ASHSB was unique in that they promoted customization of their mass-produced house plan designs to each individual site. Thus, unlike many other plan book creators, ASHSB members determined that the relationship to the site was important to the overall design and the use of these transitional indoor/outdoor spaces, a necessity. The plans designed by ASHSB members fell into one of three sizes ” four-room, five-room or six-room plan types. The maximum number of principal rooms was six. All small house designs were presented within a rendered landscaped setting showing trees, bushes, benches and other landscaping features. At least one of the following – porticoes, porches, dormers, bay windows, picture windows, port coheres, and sun porches”was used in every design produced by the ASHSB architect members. This work examines the range and type of spaces as well as the written recommendations and specifications that accompanied plan sets distributed by the ASHSB across the U.S and Canada during the early twentieth century.